Hayek's slippery slope, the stability of the mixed economy and the dynamics of rent seeking - Alves, André Azevedo (2021)
F. A. Hayek's The Road to Serfdom continues to provoke intense scholarly debate focused on the validity of Hayek's central claim that a mixed economy is inherently unstable and economic intervention will inexorably lead to totalitarianism if pursued for a sustained period. This article presents empirical evidence which shows conclusively that it is the mixed economy that has proved remarkably stable, whereas laissez-faire and totalitarian regimes have proved inherently unstable. It is argued that this empirical outcome can be explained by the dynamics of rent seeking and Hayek's failure to anticipate that the state could control more than half of national income without requiring a totalitarian apparatus to control and direct production and consumption. The implications of the failure of Hayek's argument for our conceptualisation of freedom and power in the context of the modern democratic state and our understanding of the relationship between economic and political freedom are considered.